Reduced Odds of Severe Acute Respiratory Syndrome Coronavirus 2 Reinfection After Vaccination Among New York City Adults, July 2021–November 2021. (1st July 2022) - Levin-Rector, Alison; Firestein, Lauren; McGibbon, Emily; Sell, Jessica; Lim, Sungwoo; Lee, Ellen H; Weiss, Don; Geevarughese, Anita; Zucker, Jane R; Greene, Sharon K
Abstract: Background: Belief that vaccination is not needed for individuals with prior infection contributes to coronavirus disease 2019 (COVID-19) vaccine hesitancy. Among individuals infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) before vaccines became available, we determined whether vaccinated individuals had reduced odds of reinfection. Methods: We conducted a case-control study among adult New York City residents who tested positive for SARS-CoV-2 infection in 2020 and had not died or tested positive again >90 days after an initial positive test as of 1 July 2021. Case patients with reinfection during July 2021–November 2021 and controls with no reinfection were matched (1:3) on age, sex, timing of initial positive test in 2020, and neighborhood poverty level. Matched odds ratios (mORs) and 95% confidence intervals (CIs) were calculated using conditional logistic regression. Results: Of 349 827 eligible adults, 2583 were reinfected during July 2021–November 2021. Of 2401 with complete matching criteria data, 1102 (45.9%) were known to be symptomatic for COVID-19-like illness, and 96 (4.0%) were hospitalized. Unvaccinated individuals, compared with individuals fully vaccinated within the prior 90 days, had elevated odds of reinfection (mOR, 3.21; 95% CI, 2.70 to 3.82), of symptomatic reinfection (mOR, 2.97; 95% CI, 2.31 to 3.83), and of reinfection with hospitalization (mOR, 2.09; 95% CI, .91 to 4.79). Conclusions: Vaccination reduced odds of reinfections when the Delta variant predominated. Further studies should assess risk of severe outcomes among reinfected persons as new variants emerge, infection- and vaccine-induced immunity wanes, and booster doses are administered. Abstract : Among New York City adults with severe acute respiratory syndrome coronavirus 2 infection diagnosed in 2020, unvaccinated individuals, compared with individuals fully vaccinated in the past 90 days, had 3.21 times the odds of reinfection and 2.09 times the odds of hospitalization when the Delta variant predominated. Graphical Abstract: Graphical Abstract